A Case of Closed Pilon Fracture Resulting in Soft-Tissue Necrosis and Treated with Reverse Sural Artery Flap and Circular External Fixation - Ryu Igaki; Tomohiro Yasuda; Yuki Samejima; Yuko Irie; Yuto Murakami; Taisuke Yoneya; Shinsuke Takagi; Keikichi Kawasaki; Koji Kanzaki (Case Reports in Orthopedics)
Tibial pilon fractures are difficult to treat due to articular comminution and soft-tissue injuries caused by high-energy trauma. Open reduction and internal fixation is a commonly used method of treatment. However, it has a high risk of infection and soft-tissue complications due to the extensive detachment of soft tissue. We report on a case with a tibial pilon fracture and soft-tissue necrosis that we treated using limited internal fixation combined with a circular external fixator (LIFCEF) and reverse sural artery flap (RSAF) as part of an orthoplastic approach within the orthopedic surgery department alone, which obtained good results. A 51-year-old man was injured in a motorcycle accident and transported to a nearby hospital. X-rays at the time of injury showed tibial pilon fractures (AO Foundation/Orthopedic Trauma Association 43c3.3, Ruedi–Allgower: Type III). Soft-tissue necrosis with blisters on the medial side of the lower leg (AO soft-tissue classification: IC3-MT1-NV1) was observed. In addition, the patient was referred to our hospital on day 10 of the injury. LIFCEF was chosen for treating the fracture because plate fixation was accompanied by the risk of plate exposure, soft-tissue complications, and an increased skin defect area, and RSAF was chosen to reconstruct the soft tissue defect. Four years after the surgery, the American Orthopedic Foot and Ankle Score was 92 points. X-ray alignment evaluation showed mLDTA 93° and aADTA 91°. Stage 2 arthrosis was present according to the Takakura ankle osteoarthritis classification, but the patient was able to walk without pain. Tibial pilon fractures are difficult to treat due to articular comminution and soft-tissue injuries caused by high-energy trauma. The timing and choice of treatment are crucial concerning the soft tissue.